2011
DOI: 10.20460/jgsm.2011515812
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inter Firm Knowledge Sharing on Supply Chain and Firm Performance: A Conceptual Model Proposal

Abstract: Inter-firm knowledge sharing (IKS) is identified as a significant predictor of positive performance in business relationships. On the premise that the effects of IKS have not been given the deserved scholarly attention in the SC supply chain context, this paper investigates the effects of IKS on sSupply cChain pPerformance (SCP) and fFirm pPerformance (FP). The hypothesized model is operationalised with survey data and analyzed using regression analysis. The findings add credence to the positive effects of IKS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…As mentioned by Fiol and Lyles (1985) that joint sense-making could be the first step prior the engaged parties exchange their knowledge. According to Ince and Çemberci (2011), joint sense-making is important for information sharing between buyers and suppliers because through joint sense-making, buyers and suppliers can collaborate across countries and understand each other. When buyers and suppliers have good collaboration, they are more likely to share information in order to achieve collective goals.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned by Fiol and Lyles (1985) that joint sense-making could be the first step prior the engaged parties exchange their knowledge. According to Ince and Çemberci (2011), joint sense-making is important for information sharing between buyers and suppliers because through joint sense-making, buyers and suppliers can collaborate across countries and understand each other. When buyers and suppliers have good collaboration, they are more likely to share information in order to achieve collective goals.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge sharing has been evidenced to have a positive relationship with performance in literature (e.g., [49]). In the same study [52] focused on knowledge sharing effect on SCP and evidenced the significance of the role of knowledge sharing in SC. Meanwhile, in [53] study, the authors examined the way knowledge sharing affects the performance of firms and found its significant influence on the latter.…”
Section: B Knowledge Sharing and Supply Chain Performancementioning
confidence: 86%
“…Reference [36] described the supply chain as encapsulating the entire activities relating to the goods/information flow beginning from raw materials sourcing to the delivery to the end user. In the manufacturing context, manufacturers are generally critical in determining the SC goals as a result of which, they delineate the performance of supply chain.…”
Section: Supply Chain Performancementioning
confidence: 99%
“…These challenges include the provision of products or services at the right place, at the right time and at the lowest possible cost (Jagtap et al , 2021). Therefore, the aim of most organizations across the globe is not only about improving their organizational efficiencies, but to give critical attention to their entire supply chain (Ince and Çemberci, 2011). According to Gopal et al (2019), the objective of supply chain management (SCM) is to ensure the supply chain competitiveness of an organization.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gopal et al (2019), the objective of supply chain management (SCM) is to ensure the supply chain competitiveness of an organization. Consequently, the understanding of effective SCM has begun to be very important for most businesses across the globe (Fawcett et al , 2007; Ince and Çemberci, 2011; Luo et al , 2013). This is because effective SCM exerts a significant impact on organizational performance (Gopal et al , 2019; Luo et al , 2013).…”
Section: Introductionmentioning
confidence: 99%